EVALUASI KEGIATAN PEMBELAJARAN PADA LEMBAGA PENDIDIKAN TINGGI ISLAM: STUDI KASUS STAIN JURAI SIWO METRO - Sudin, Mokhtaridi (P3M STAIN Jurai Siwo Metro, 2011)
This article examines the evaluation of learning process as one of determinant variables in achieving the objectives of educational system conducted in Indonesian Islamic higher educational institution. It aims therefore to give a rich description on the ideal process of learning activities through the evaluation study. For the purpose of study, the writer uses Jurai Siwo State Islamic College (STAIN) as the object of study.The writer brings all these facts to state that the conduct of learning activities in STAIN Jurai Siwo does not optimize the taxonomy of educational objectives. This can be seen from both external and internal points of view. For the former, STAIN Jurai Siwo does not hitherto have an âexcellentâ accredited study program. Moreover, there is still no formal satisfactory statement from any single educational institution, government or company as to the existence of STAINâs alumni working for them. For the latter, the institution is unable to implement the standards of operational procedures (SOP) in a proper way albeit it has the so-called quality assurance system. In addition, the section of quality assurance, which is founded for increasing academic excellence in the institution, is also unable to build an effective cooperation among all the stakeholders.Â Â Keywords: Evaluasi kegiatan pembelajaran, taksonomi pendidikan, pendidikan holistik, lembaga pendidikan tinggi Islam